Success in Management Consulting and the Concept of Eliteness Motivation - Miner, John B. (Academy of Management Journal, 1971)
Two hypotheses regarding the sources of success in management consulting are investigated using biographical data in a predictive design. The hypotheses deal with: (1) a total life pattern of successful endeavor, and (2) a maximal prior exposure to top management culture. The data only partially support the hypotheses. Rather, the concept of elite-ness motivation seems most adequate to explain the results obtained.